Ebola Virus Disease in the Era of One Health and Global Preparedness: Evolving Epidemiology, Genomic Surveillance, and Future Challenges - Francesco De Maria; Francesco Branda; Ivailo Alexiev; Dong Keon Yon; Ayşe Banu Demir; Giancarlo Ceccarelli; Fabio Scarpa; Massimo Ciccozzi; Alessandro Russo (Infectious Disease Reports, 2026)
Ebola virus disease (EVD) remains one of the most severe viral hemorrhagic fevers, with recurrent outbreaks challenging global healthcare systems. This narrative review traces the evolving epidemiology of EVD from the first recognized outbreaks in 1976 to the ongoing 2026 Bundibugyo virus public health emergency in the Democratic Republic of the Congo (DRC) and Uganda. Over nearly five decades, the recognized range of Ebola outbreak contexts and amplification mechanisms has broadened considerably: rural zoonotic spillovers remain the predominant mode of emergence, but the scale and reach of subsequent transmission increasingly depend on where introductions occur, on delays in detection, on population mobility, on ecological disruption, on armed conflict, on healthcare-associated transmission, and on viral persistence in survivors. Major advances in molecular epidemiology and genomic surveillance have improved outbreak investigation, enabling real-time transmission reconstruction and detection of survivor-linked resurgence. Vaccination, particularly ring vaccination with rVSV-ZEBOV, has shown high effectiveness against Zaire ebolavirus, yet vaccine equity gaps and the absence of licensed vaccines for Sudan virus and Bundibugyo virus remain critical vulnerabilities, though new candidate vaccines and therapeutics for Bundibugyo virus entered clinical evaluation in mid-2026. Artificial intelligence and digital technologies, including AI-assisted early warning systems, portable sequencing, drones, blockchain, and mobile health platforms, offer promising tools for outbreak preparedness, but robust evidence of their real-world operational impact during filovirus outbreaks remains limited, and their deployment in low-resource settings faces substantial barriers related to infrastructure, literacy, data costs, and governance. Integrated preparedness frameworks that combine ecological surveillance, resilient healthcare systems, community engagement, and international coordination under a One Health umbrella are increasingly viewed as a strategic necessity. The 2026 Bundibugyo outbreak reaffirms that despite decades of lessons, structural weaknesses in surveillance, response timeliness, and community trust continue to recur. Sustainable, multi-year financing, diversified vaccine platforms, regional manufacturing, and local co-design of digital tools are essential to translate lessons into lasting change. Preparedness is best understood as a continuous process rather than a reactive state.